Income inequality, redistribution and domestic terrorism - Tim Krieger; Daniel Meierrieks (World Development, 2019)
We analyze the effect of income inequality on terrorism for a sample of 113 countries between 1984 and 2012. We provide evidence, robust to various methodological changes (e.g., the use of instrumental-variable approaches), that higher levels of income inequality are associated with more domestic terrorism. Analyzing the underlying transmission channels, we find that this effect is in parts due to the ill effects of income inequality on institutional outcomes (e.g., corruption) which in turn motivate domestic terrorism. We also investigate whether redistributional efforts can be effective in reducing terrorist activity. We find that countries that redistribute more see less domestic terrorism, in parts because redistribution improves institutional conditions. In light of this latter finding, we discuss the implications of our analysis for policymakers who want to counter domestic terrorism through redistributive policies.
Keywords: D74; I38; O15; C36; 330; income inequality; terrorism; Gini coefficient; relative deprivation; redistribution